State formation and the establishment of non-Muslim hegemony : post-mughal 19th-century Punjab - Rishi Singh (Sage Publications India Pvt. Ltd., 2015)
"This book examines the state formation process in Panjab and the qualitative change in the hegemony of elites from Muslims to non-Muslims in the first half of the nineteenth century. It argues that after the emergence of the Sikh faith in the fifteenth century, there appeared on the social fabric of elites two distinct categories, the Muslim and the non-Muslim"--Provided by publisher.